Measurement of body composition should become routine in nutritional assessment of children with cerebral palsy. (1st April 2015) - Sullivan, Peter
<x xml:space="preserve">Abstract</x> This commentary is on the original article by Finbråten et al. on pages 858–864 of this issue.